The Relationship between 25-Hydroxyvitamin (OH) D Levels and Nutritional Status in Children with Family History of Atopy - Hardaningsih, Galuh; Ardiaria, Martha; Pratiwi, Rina; Tjandra, Kevin Christian; Putra Respati, Danendra Rakha; Setiawan Limijadi, Edward Kurnia (International Journal of Child Health and Nutrition, 2024)
Background: Deficiency in vitamin D can result in growth retardation and skeletal abnormalities. Children with a familial history of atopy are at a heightened risk of atopic dermatitis and growth impairments. These growth disorders associated with atopy may stem from chronic inflammation and nutrient malabsorption. Evidence suggests vitamin D deficiency may exacerbate atopic conditions, further impacting growth and development. Thus, this study investigates the link between vitamin D levels and anthropometric status in children with a history of atopy. Method: Seventy-eight patients were selected and recruited from Diponegoro University Hospital between June and October 2021. Inclusion criteria comprised pediatric patients aged between one month and six years, either diagnosed with atopic disease or having a family history of the ailment. Exclusion criteria included chronic illnesses other than atopic disease, ongoing infections, and lack of medical records. Nutritional status was assessed using HAZ, WAZ, and WHZ. Additional data on vitamin D levels, dietary intake (calories, protein, and fat), iron and zinc sufficiency, and history of exclusive breastfeeding were also collected. Results: The study encompassed 78 children. Nutritional assessment revealed that 63 children had good nutritional status, 10 were overweight, 2 were malnourished, and 3 were severely malnourished. The 25-OH D level was 3 children classified as deficient, 15 as insufficient, and 60 as having normal levels. Analysis bivariate indicated no significant impact of vitamin D levels on anthropometric parameters. This lack of significant correlation was consistent in both the general population (n=78) and those with atopic manifestations (n=56), suggesting that vitamin D levels do not significantly affect growth parameters in this pediatric cohort. Conclusions: This study concludes that vitamin D levels have no significant impact on anthropometric parameters in children, irrespective of their atopic status. Despite the acknowledged role of vitamin D in growth and development, the data suggests that vitamin D levels do not substantially influence growth parameters in this pediatric cohort with a history of atopy. Further investigation may be warranted to explore other potential factors influencing growth in children with atopic conditions.